2008
DOI: 10.1080/07853890701879790
|View full text |Cite
|
Sign up to set email alerts
|

Coronary angioplasty in drug eluting stent era for the treatment of unprotected left main stenosis compared to coronary artery bypass grafting

Abstract: PCI with DES for selected LMCA disease patients results in short- and midterm outcomes comparable to results of CABG in general. PCI is a viable therapeutic option in selected patients with LMCA stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…Second-generation drug-eluting stents have been shown to reduce TVR rates significantly in all lesions when compared with bare metal stents or first-generation drug-eluting stents. 32,33 Adherence to optimal medical therapy may influence the occurrence of post-CABG cerebrovascular events. Recent analyses of data from a health plan database revealed that CABG patients were less likely to be on statins or angiotensin converting enzyme inhibitors, which in turn puts them at higher risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Second-generation drug-eluting stents have been shown to reduce TVR rates significantly in all lesions when compared with bare metal stents or first-generation drug-eluting stents. 32,33 Adherence to optimal medical therapy may influence the occurrence of post-CABG cerebrovascular events. Recent analyses of data from a health plan database revealed that CABG patients were less likely to be on statins or angiotensin converting enzyme inhibitors, which in turn puts them at higher risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the 2011 PCI guideline and Data Supplements 3 and 4 12 revealed that 4 randomized trials [13][14][15][16] and 8 cohort studies [17][18][19][20][21][22][23][24] comprised the evidence for the new Class IIa recommendation for PCI to improve survival in patients with ULMCAD, whereas 7 older studies formed the knowledge base to show that CABG confers a survival advantage over MT in patients with ULMCAD. [2][3][4][5][6][7][8] The 19 studies used predefined enrollment criteria and were published in peer-reviewed journals.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the second premise comes from 4 randomized trials [13][14][15][16] and 8 cohort studies, [17][18][19][20][21][22][23][24] all reported during the past 7 years.…”
Section: Clinical Perspective On P 2185mentioning
confidence: 99%
See 2 more Smart Citations